2013
DOI: 10.1007/s13277-013-1043-1
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone and imidapril alone or in combination alleviate muscle and adipose depletion in a murine cancer cachexia model

Abstract: Rosiglitazone (RGZ) and imidapril improve cancer cachexia via different mechanisms. Therefore, we hypothesized that combination therapy of RGZ+imidapril would further attenuate cancer cachexia in vivo. After injection with colon-26 adenocarcinoma for 9 days, BALB/c mice were randomly divided into the following four treatment groups for 7 days (n = 8 per group): (1) placebo, (2) RGZ, (3) imidapril, and (4) RGZ+imidapril. Eight healthy control animals were also assessed. Body weight, tumor volume, gastrocnemius … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 52 publications
4
5
0
Order By: Relevance
“…At a daily dose of 10 mg/kg body weight, it attenuated the weight loss . Similar effects were observed in another experiment performed in the murine cancer cachexia model, where imidapril attenuated the muscle and adipose tissue depletion . Transfer to patients with cancer cachexia was already conducted in a randomized placebo controlled trial, but the findings were not published yet …”
Section: Therapeutic Strategies For Cardiac Cachexiasupporting
confidence: 59%
See 1 more Smart Citation
“…At a daily dose of 10 mg/kg body weight, it attenuated the weight loss . Similar effects were observed in another experiment performed in the murine cancer cachexia model, where imidapril attenuated the muscle and adipose tissue depletion . Transfer to patients with cancer cachexia was already conducted in a randomized placebo controlled trial, but the findings were not published yet …”
Section: Therapeutic Strategies For Cardiac Cachexiasupporting
confidence: 59%
“…75 Similar effects were observed in another experiment performed in the murine cancer cachexia model, where imidapril attenuated the muscle and adipose tissue depletion. 103 Transfer to patients with cancer cachexia was already conducted in a randomized placebo controlled trial, but the findings were not published yet. 104 Another attractive concept for prevention of body wasting is the exercise training that is expanding over a variety of chronic disease, including the cachexia patients.…”
Section: Preventive Strategies For Body Wasting and Cardiac Cachexiamentioning
confidence: 99%
“…The development of a cancer leads to a loss of energy balance in response to the intensification of catabolism, which, in turn, results in cancer-associated cachexia. 113 The lower cachexia index and reduced body weight loss in WTG rats compared to the WT group confirmed our previous studies demonstrating the beneficial effects of l -glutamine supplementation in the diet, particularly in the small intestine. 33,37…”
Section: Discussionsupporting
confidence: 88%
“…One of the most marked negative effects of cancer is cachexia, a complex syndrome characterized by anorexia, and increased proteolysis with loss of muscle and adipose mass. 110 The prevalence of cachexia in gastric, pancreatic, lung, advanced colorectal, or prostate neoplasias is more than 50%, whereas it is estimated to be between 30% and 50% in non-Hodgkin lymphoma, breast cancer, sarcomas, and leukemias. 11 Moreover, a cachectic status worsens the prognosis and implies increased mortality, being responsible for the death of 22% of cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Several preclinical studies have demonstrated that ACEi can control cancer cachexia in different rodent models (13,105,106), while imidapril had no beneficial effect on cardiac wasting in a rat hepatoma cancer cachexia model (107). In a subcutaneous murine colon cancer model, the direct renin inhibitor aliskiren had potent anti-cachexia effects.…”
Section: Cachexiamentioning
confidence: 99%